2007
DOI: 10.1093/jat/31.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Amphetamine, Methamphetamine, and Hydroxyamphetamine Derivatives in Urine by Gas Chromatography-Mass Spectrometry and Its Relation to CYP2D6 Phenotype of Drug Users

Abstract: Amphetamine, a CYP2D6 substrate, is widely used by truck drivers, and the extent to which different people metabolize the drug has only been determined in an isolated or reduced number of samples. A gas chromatography-mass spectrometry method is implemented to simultaneously determine amphetamine, methamphetamine, and hydroxyamphetamine in the urine of drug users. This method is a useful contribution to a well-established field. The main improvements are the use of liquid-liquid extraction, the trapping of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Thus, extrapolation of neurotoxicity findings involving the P450 system from animals to humans must be done cautiously. While no studies, to our knowledge, have investigated links between amphetamine metabolite concentrations and neurotoxicity in humans, it has been demonstrated that EM have greater urinary excretion of the hydroxy metabolite, followed by IM, and then by PM (Miranda, Sordo, Salazar, Contreras, Bautista, & Rojas Garcia, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, extrapolation of neurotoxicity findings involving the P450 system from animals to humans must be done cautiously. While no studies, to our knowledge, have investigated links between amphetamine metabolite concentrations and neurotoxicity in humans, it has been demonstrated that EM have greater urinary excretion of the hydroxy metabolite, followed by IM, and then by PM (Miranda, Sordo, Salazar, Contreras, Bautista, & Rojas Garcia, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Amphetamines and related compounds have usually been extracted from urine samples by liquid-liquid extraction (LLE) [17][18][19], supercritical fluid extraction (SFE) [20], solid-phase extraction (SPE) [21,22], and solid-phase microextraction (SPME) [23][24][25]. However, there are several disadvantages of conventional extraction procedures such as LLE and SPE.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several methods, such as gas chromatography (GC), 3,4 high performance liquid chromatography (HPLC), 5 GC-mass spectrometry (MS), [6][7][8][9][10][11][12] HPLC-MS, 13,14 capillary electrophoresis (CE), 15 and CE-MS, 16 along with sample preparation methods have been developed for the determination of amphetamine and related compounds at low concentration in biological matrices. In order to eliminate interferences from the biological matrices, liquid-liquid extraction (LLE), [17][18][19] supercritical fluid extraction (SFE), 20 solid-phase extraction (SPE), 21,22 and solid-phase microextraction (SPME) [23][24][25] have been proposed. However, there are several disadvantages for conventional extraction procedures such as LLE and SPE.…”
Section: Introductionmentioning
confidence: 99%